Spamming in Indonesian Criminal Law Perspective: The Nature Elements - Pamungkas, Alex Candra (Law Research Review Quarterly, 2021)
Internet has become something important in the development of means of communication. One of the communication facilities found on the internet is internet relay chat or what is often known as chat. Real-time chat applications are often misused for the purposes of spreading viruses, promotions, and other interests known as spam. Spamming is the sending of unwanted messages by someone who has a chat account. This causes the account owner to feel uncomfortable with these conditions. Spamming or generally referred to as junk messages is one of the crimes that arise along with the development of technology. Currently, in Indonesia there are no specific regulations that regulate spam. Therefore, a criminal law policy is needed to overcome this problem.